Quorum sensing in biofilm-mediated heavy metal resistance and transformation: environmental perspectives and bioremediation - Mondal, Subhoshmita; Melzi, Alice; Zecchin, Sarah; Cavalca, Lucia (Frontiers in Microbiology, 2025)
Quorum sensing is a fundamental mechanism of bacterial cell-to-cell communication that enables microbial communities to adapt to environmental stresses. Although the role of quorum sensing in biofilm formation and heavy metal resistance has been studied across various bacterial species, significant research gaps remain regarding the specific quorum sensing-regulated metabolic pathways involved in heavy metal resistance and transformation, as well as their functional roles in bioremediation. This review provides a comprehensive overview of the connection between quorum sensing and heavy metal resistance and transformation, considering both cellular and ecological perspectives. It highlights recent advancements in understanding quorum sensing-regulated biofilm dynamics and identifies a lack of knowledge related to quorum sensing-mediated heavy metal resistance in natural ecosystems. Furthermore, innovative quorum sensing-based strategies for optimizing bioremediation are explored. By emphasizing the ecological and practical implications of quorum sensing-driven bioremediation, this review aims to contribute to the development of more effective and sustainable approaches for mitigating heavy metal pollution.